THE STUDY ACTIVITIES OF HISTORIOGRAPHICAL SOURCES IN POLITICAL PARTIES CONNECTION WITH THE ISSUE OF NATIONALITY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
.The article highlights the work of scientists studying the historical socio-political movements, the formation and establishment of political parties in Kyrgyzstan in the early 90s. And opinions of scientists as well as who presented the programs of the first public organizations of socio-ethnopolitical significance, which had a national character, had fought for independence and sovereignty. Within, analyzing domestic and foreign historical works, scientists who studied the phenomenon of the party from different points of view reflected historical facts, various events and phenomena, and also works in which they had published their personal views, opinions and assumptions. In the quoted sources have highlighted the features of early political, social and national movements in Kyrgyzstan, primarily the formulation of socio-economic issues, the activities of political parties demanding the gratuitous transfer of land for the construction of private homes.
Keywords: political party, public organizations, social, economic, political problems, national community, scientists, works, scientific sources